AKAR PEMIKIRAN REALISME DALAM HUKUM ISLAM - Yusuf, Anwar Sofiyudin (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2015)
Talking about realism in Islamic law, it is still a very interesting to be studied, especially if it confronted to the characteristic of idealism in Islamic law. As if they become two magnetic poles which will never be united, realism can be a threat to the ideals of Islamic law itself. In the idealism view, reality must be subject to the law, but in realism view, it is the opposite, it mean that the law should follow reality. However, it is not important whether the law follows the reality or otherwise. The faithful law should follow reality. Because in the end, the legal system is needed to be resolved in every case that occurs in the community. Sosial reality in fact be an important entity in influencing the formation of Islamic law, in the form of fatwas of scholars, Judges decision or the books of fiqh, and not least the Quran and Hadith.